Feasibility of a brief mindfulness-based program for burnout in pain healthcare professionals - Server, Anna; Suso-Ribera, Carlos; Pérez-Carrasco, Marcos; Medel, Javier; Mesas, Ángela; Ayora, Alfonso; Gracia, Rosa Maria (Frontiers in Psychology, 2022)
Introduction: Stress inherent to health care, which is characterized by work overload and shortage of specialized staff, is associated with decreased quality of life and suboptimal patient care. Mindfulness-based programs have proved to be effective in reducing stress in healthcare providers. This study aims to assess the feasibility of an 8-week mindfulness program to reduce the burnout levels of the staff of a pain clinic in a tertiary public hospital. Materials and methods: A longitudinal study with a within subject pre/post-intervention design, consisting of daily face-to-face 10-minute sessions and the creation of a virtual group using a social media platform. Variables measured: burnout, mindfulness, empathy, self-compassion, and demographic characteristics. Results: Program feasibility (i.e., reach, adherence, acceptability, and preliminary effectiveness) was evaluated in 10 participants (6 physicians, 2 nurse practitioners, 1 nursing assistant, and 1 administrative). The results revealed a high reach (i.e., participation rate of 90%), excellent adherence to the program (daily practice 95% of times), and very good acceptability of the group format and satisfaction with most treatment components. Regarding potential effectiveness, we report the results of the Wilcoxon signed-rank tests and its associated effect size (r). We observed improvements in mindfulness and all its subscales (-2.077≤Z ≤-2.703, 0.69≤r≤0.90, all p<.05) except for non-reactivity and all subcomponents of self-compassion (-2.501≤Z≤-2.611, 0.83≤r≤0.87, all p<.05) but not on its global self-compassion score. Empathy and burnout did not change. In an exploratory manner, however, we found significant reductions in the burnout component of emotional exhaustion, but only in physicians (Z=-2.201, p=.028, r=0.73). Discussion: We believe that the 8-week mindfulness-based program described in the present investigation might be a feasible and potentially effective method that can be easily implemented to reduce burnout and promote mindfulness in specialized pain clinics.